Neuraminidase-mediated enhancement of Streptococcus pneumoniae colonization is associated with altered mucus characteristics and distribution - Matthew T. Montgomery; Mila Ortigoza; Cynthia Loomis; Jeffrey N. Weiser (mBio)
ABSTRACT Upon entry into the upper respiratory tract (URT), Streptococcus pneumoniae (Spn) upregulates neuraminidases (NA) that cleave sialic acid (SA) from host glycans. Because sialylation is thought to contribute to the physical properties that determine mucus function, we posited that Spn directly alters host mucus through NA activity. By directly imaging the colonized URT, we demonstrated NA-mediated alterations to the characteristics and distribution of mucus along the respiratory epithelium, where colonizing bacteria are found. Mucus exposed to NA showed increased localization within goblet cells and lining the glycocalyx. By contrast, NA-naïve mucus was more likely to be observed sloughing away from the epithelial surface. We also visualized Spn in the URT and observed that NA promoted efficient bacterial localization to the firm mucus layer overlying the glycocalyx, whereas NA-deficient Spn was associated more with loose mucus. By facilitating tighter association with the glycocalyx, NA promoted increased Spn colonization density. The magnitude of the NA-mediated effect on colonization was widened during late colonization by increased evasion of host-mediated clearance mechanisms. Thus, Spn-encoded NAs directly modify the host environment by desialylating mucus, which allows close interaction with mucus at the epithelium, and this is associated with enhanced bacterial colonization.IMPORTANCEAlthough severe illness and death caused by Spn result from secondary invasive diseases including pneumonia, sepsis, and meningitis, stable colonization of the upper respiratory tract (URT) is a prerequisite to invasive disease. Therefore, understanding host-Spn dynamics during asymptomatic colonization of the URT is warranted with respect to the pathogenesis of Spn disease. In this study, we found that Spn NA activity directly alters mucus characteristics that result in increased density and duration of URT colonization. Therefore, targeting Spn NA activity during URT colonization may be a viable strategy to mitigate Spn infection.